P29 Endothelial cell NF-kB activation is increased in human idiopathic PAH. (16th November 2010) - Price, LC; Caramori, G; Dorfmuller, P; Perros, F; Zhu, J; Shao, D; Humbert, M; Adcock, I; Wort, SJ
Abstract : Background: Pulmonary arterial hypertension (PAH) is associated with pulmonary vascular inflammation, and several of the inflammatory genes involved are regulated by nuclear factor-kB (NF-kB). NF-kB is a heterodimer of p65 and p50 subunits which, upon activation, translocate into the nucleus and binds to target gene promoters. NF-kB activation in PAH has not been examined in detail to date. We assessed NF-kB activation by immunohistochemical analysis of nuclear p65. Methods: Samples were obtained from South Paris University from patients with severe idiopathic PAH (IPAH) following lung transplantation (n=10) and from control subjects undergoing lobectomy or pneumonectomy (n=10). Tissue blocks were fixed and paraffin-embedded, 4-mm thick sections underwent immunoperoxidase double staining for macrophage (CD68+)/p65, using mouse anti-human CD68 (Dako; 1:100 dilution) and rabbit anti human p65 (Santa Cruz Biotechnology; 1:50 dilution), before detection with chromogen fast red and counterstaining with haematoxylin. Vessels of interest were defined and quantitative scoring of nuclear p65 immunostaining of ten randomly selected pulmonary arteries per slide performed by a researcher blinded to the groups. Data are expressed as median and IQR, and the groups were compared by the Kruskal–Wallis or Mann–Whitney U test. Results: (1) PAH specimens showed co-localisation of p65 within CD68+ macrophages in 75.4 (64.8–84.6)% of samples. Airway epithelium, neutrophils and lymphocytes were also positive for p65. (2) Pulmonary arterial medial thickness was increased in PAH compared to controls, at 33.7 (18.8–67.9)% in vessels 100–250 mm external diameter (E.D.) and 27.2 (14.8–44.2)% in vessels 250–500 mm ED, vs 17.7 (11.2–30.3)% and 14.9 (11.8–17.8)% in controls (p<0.0001 between groups). (3) Nuclear p65 was present in pulmonary artery endothelial cells (EC) but not other vascular cells including pulmonary artery smooth muscle cells in PAH: 53.9 (0–100)% of vessels 100–250 mm E.D. and 53.1 (0–100)% of those 250–500 mm E.D. scored EC p65 positivity in PAH compared to 7.5 (0–25.0)% in 100–250 mm ED and 4.7 (0–21.1)% in 250–500 mm ED in controls (p<0.0001 between groups) (Abstract P29 Figure 1 ). Conclusion: NF-kB activation is present in macrophages and pulmonary arterial endothelial cells in pulmonary arteries of 100–500 mm ED in patients with PAH.